Agroclimate prediction and advisory for Ethiopian agricultural extension - Ahmed, Jemal Seid; Tesfaye, Kindie; Demissie, Teferi Dejene; Tamene, Lulseged D.; Gebremariam, Temesgen; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
To date, the performance of Belg rainfall has been mixed with favorable conditions in the southern and eastern half of Ethiopia's Southern Nations, Nationalities and Peoples Region (SNNPR), and adjoining western areas of Oromia. However, in eastern and southern Tigray, eastern Amhara, and northern Afar, seasonal rainfall has been erratic, delayed in onset, and slightly below average. As a result, Belg planting was delayed in these areas, and in some cases, farmers were deterred from planting despite heavy April rainfall. However, the favorable Gu/Genna rains (March to May) have supported relatively favorable production prospects for pastoral and agropastoral communities of Somali and southern Oromia.